Mejora en la producción oral de los alumnos del nivel básico 05 del idioma Inglés del CPAT El Cultural de la ciudad de Tarapoto a través de la utilización del Método ECRIF en el año 2013 - Paredes Gonzales, Tony Hanz (2013)
This thesis makes the study on improving the oral production of forty-two EFL students of Basic 05 level of The CPAT El Cultural through the application of the ECRIF method that is based on the psychological foundations of constructivism and collaborative learning in the teaching of foreign languages. To reach this goal, we developed 12 learning sessions using the ECRIF Method, collecting the results of its application through the evaluation sheets of oral production, divided into five indicators (fluency, comprehension, pronunciation, grammar and vocabulary). The learning sessions were performed with activities that exploited the expression of lite experiences of each participant through movement, games, discussions and drawings. The results showed an increase in each of the 5 criteria of oral production, improving the linguistic and communicative competence of students. According to the conducted statistical analysis, it was verified the research hypothesis, revealing that t value was considered statistically significant. Through this study, it was possible to draw conclusions that are intended to contribute to the area of teaching and learning of English as a foreign language it was proved the effectiveness of the ECRIF method. it is proposed, therefore, that in the design of learning sessions for English language classes, it is integrated and implemented this method because it is very conducive to learning English as a foreign language.